Neurologic Complications of Hereditary Hemorrhagic Telangiectasia - Oliveira,Ana Andrade (2021)
Abstract Hereditary hemorrhagic telangiectasia is a rare disorder affecting the vasculature of several organs. Stroke and brain abscess are rare complications associated with paradoxical embolism due to pulmonary arteriovenous malformations. We describe a case of a 45-year-old woman that presented those two life-threatening neurologic complications within a year; this occurred because the pulmonary arteriovenous malformations were not addressed after the diagnosis of hereditary hemorrhagic telangiectasia. We aim to highlight the neurologic complications related to pulmonary arteriovenous malformations and focus on the importance of early detection and manage-ment of patients with hereditary hemorrhagic telangiectasia and their relatives.